Independent transitions to fully planktonic life cycles shaped the global distribution of medusozoans in the epipelagic zone - Manon Boosten; Camille Sant; Ophélie Da Silva; Samuel Chaffron; Lionel Guidi; Lucas Leclère (Proceedings of the National Academy of Sciences, 2025)
Life history traits influence marine species dispersal and habitat colonization. Medusozoans (jellyfish and siphonophores) exhibit diverse life cycles, evolved from an ancestral cycle alternating between a benthic polyp and a pelagic medusa. Despite their ecological importance, factors shaping medusozoan distribution remain poorly understood. By integrating metabarcoding and environmental data from the Tara Oceans expedition with life history traits, we provide global evidence supporting the longstanding hypothesis that benthic polyp presence/absence is a key factor influencing the distribution and abundance of planktonic medusozoans in the surface ocean. We inferred on a time-calibrated phylogeny of Medusozoa multiple transitions to a fully planktonic (holoplanktonic) life cycle, either through polyp loss, acquisition of drifting polyps, or development of polyps parasitizing pelagic organisms. We could associate each transition with a shift toward offshore habitats and the emergence of globally dominant Operational Taxonomic Units (OTUs), whose abundance far exceeds that of any nonholoplanktonic medusozoans in the planktonic realm. The prevalence of holoplanktonic medusozoans in terms of abundance and diversity is broadly observed in coastal and offshore environments, peaking over greater bathymetric depths in tropical and subtropical regions. We show that holoplanktonic and nonholoplanktonic groups interact with distinct yet compositionally similar planktonic communities. Holoplanktonic OTUs occupy more peripheral positions in a plankton interactome, suggesting greater flexibility in biotic interactions, an adaptive trait in rapidly changing planktonic ecosystems. These findings highlight how life cycle evolution shaped the global distribution of medusozoans and suggest that variations in life history may significantly influence how medusozoans respond to global environmental changes.